Menggali peran digital fitness influencer terhadap parasocial interaction dan fan citizenship behaviour - Mubarak, Nu’man; Kusumawati, Andriani; Raharjo, Kusdi (Faculty of Communications Science, Dr. Soetomo University, 2021)
This article elucidate the concept of fan citizenship behaviour can be influenced by digital fitness influencers and parasocial interactions. This article uses a systematic literature review approach to clarify the concept fan citizenship behaviour by integrating source credibility theory and social exchange theory. The results provide 39 articles extend an overview of digital fitness influencers in holistic, how fitness influencers build relationships in a parasocial and resiprokal. Digital fitness influencers share content through photos, videos and interact with fan through comments or short messages, and fan form imaginary relationships called parasocial relationships. From the relationships, fan gratify their psychological necessity such as pleasurement, cultivate loyalty and commitment to digital fitness influencers.